Analysis of Health Risk Factors in Children Based on Dietary Habit at SDN Cempaka Putih Barat 07 Timur, Central Jakarta - Azizatun Munawaroch; Omega DR Tahun (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The incidence of anemia is a health problem that occurs evenly throughout the world, especially in developing countries where it is estimated that 30% of the world's population suffers from anemia. Meanwhile, the incidence of anemia in Indonesia reaches 29.0%. The effects of anemia on children include that children tire easily, decrease concentration in learning, are susceptible to infection, decrease in cognitive abilities, and if it occurs in school children it will reduce learning capacity and ability. The purpose of this study was to determine the relationship between diet and the incidence of anemia in school-age children. This type of research is quantitative analytic, cross-sectional design. This research was conducted at SDN Cempaka Putih Barat 07, Central Jakarta in October 2022 - January 2023. The population in this study were all elementary school children, the sample size was 75 respondents. How to take samples using systematic random sampling method. Of all the respondents studied, it was found that there were 22.7% of children who had anemia. The results of the chi square test showed that dietary pattern was related to the incidence of anemia in children, iron intake (p value=0.000; OR=8.8), protein intake (p value=0.049; OR=3.5) and vitamin C intake. (p value=0.033; OR=3.8). The health Center needs to optimize educational programs for elementary school children, parents and teachers about the dangers of anemia in children and efforts to prevent / treat anemia in children.